Autoimmune pancreatitis, pancreatic and extrapancreatic cancer (AIPPEAR): a multicentre, retrospective study protocol - Jonas Rosendahl; Ivonne Regel; Julian Cardinal von Widdern; Cecilie Siggaard Knoph; Karri Kase; Christoph Ammer-Hermenau; Sara Nikolic (BMJ Open)
Introduction Autoimmune pancreatitis (AIP) mainly manifests in two distinct forms with different clinical, serological and prognostic characteristics. Previous studies indicated a higher risk of malignancy in AIP patients compared with the general population. However, a direct comparison of cancer incidence in AIP patients with controls from the general population has not been conducted yet.Methods and analysis This is an international, multicentre, retrospective study on patients diagnosed with AIP after 2005. Retrospective data regarding demography, AIP characteristics and cancer incidence will be extracted from the medical files of AIP patients. The primary outcome is the standardised incidence ratio of any first invasive cancer after AIP diagnosis compared with the general population. The expected number of cancers in the general population will be determined using the ‘Cancer Incidence in Five Continents Volume XI’ registry. Secondary outcomes are the prevalence of all cancer diagnoses within 12 months prior to AIP diagnosis and AIP features associated with a cancer diagnosis.Ethics and dissemination This study was approved by the ethics committees of the autoimmune pancreatitis, pancreatic and extrapancreatic cancer (AIPPEAR) core group centres (Halle (Saale), Germany; Aalborg, Denmark; Tartu, Estonia; Munich, Germany; Göttingen, Germany; Maribor, Slovenia, with the following reference numbers: 2023–204, 2023–0 29 953, 382 /T-3, 24–0768, 9/7/23, UKC-MB-KME 59/23, respectively). Where required, the study protocol will be reviewed and approved by the ethics committees of participating centres in compliance with local regulations. Data will be stored in an electronic case report form within REDCap. In this context, the AIPPEAR core group will share joint responsibility for the data. All results from this study will be submitted to international, peer-reviewed journals and presented at international conferences.Trial registration number NCT06328101.